Football GOATs : the greatest athletes of all time - Berglund, Bruce R. (North Mankato, Minnesota : Capstone Press, a Capstone imprint, 2022)
How do you pick football's GOATs? Is Tom Brady the greatest quarterback? Is Alan Page the greatest defensive tackle? Who's the all-around champ? It comes down to stats, history, and hunches. Read more about some of the legends of football and see if you agree that they're the greatest of all time.
How to pick football's greatest -- Defense -- Special teams -- Offense.
Includes bibliographical references (page 31) and index.
4.8
3-6
Keywords: Football players -- Juvenile literature; Football -- Records -- Juvenile literature; Football -- Statistics -- Juvenile literature; Football players; Football; Sports records; Football -- Statistics